Pengaruh Restitusi Kelebihan Pembayaran Pajak Pertambahan Nilai Pada Kantor Pelayanan Pajak Pratama Jakarta Penjaringan - Riftiasari, Dinar (Universitas Bina Sarana Informatika, 2019)
The Value Added Tax is central tax, tax payment amount payable by the amount of the tax credit shows the amount of excess have been made that should tax refunds. The purpose of this study was to determine the effect of value added tax restitution of value added tax revenue. Method used in the study is a quantitative method. This research is value added tax restituition that occurred in the Tax Office Pratama Jakarta Penjaringan the implementation of restitution does not has any effect toward value added tax revenue. The Standar Operating Procedures of value added tax restitution in the Tax Office Pratama Jakarta Penjaringan is Standar Operating Procedures No KPP50-0004. Keywords: Value Added Tax , Restitution, Tax Revenues